PELAKSANAAN PROGRAM DUKUNGAN PSIKOSOSIAL MELALUI PSYCHOLOGICAL FIRST AID (PFA) OLEH RELAWAN BENCANA ERUPSI SEMERU KABUPATEN LUMAJANG - Kharima, Nadya; Yulianti, Yulianti; Anjani, Aninda Dwi (UIN Sunan Kalijaga Yogyakarta, 2022)
The Semeru mountain eruption disaster that occurred in Lumajang Regency which occurred on December 4, 2021 left many sorrows including loss of property, relatives, and prolonged trauma. Therefore, volunteers are present to provide support to disaster victims with various forms of assistance such as evacuation assistance, logistics, warm posts, free laundry and psychosocial support. Currently, psychosocial support programs appear in the form of Psychological First Aid (PFA). Based on this, this study focuses on seeing how the implementation of psychosocial support programs through PFA by volunteers of the mount semeru eruption disaster in Lumajang regency. The research methods in this study use descriptive qualitative research using data collection through interviews and documentation studies. Based on the results of the study, it can be concluded that there are eight components of PFA implementation that have been implemented by volunteers, namely (1) contact and involvement; (2) safety and comfort; (3) stabilization; (4) information collection: needs and concerns (5) practical assistance; (6) relationship with social support; (7) information about coping; and (8) interrelationships with collaborative services. And there are obstacles felt by volunteers are related to adaptation to language, because volunteers are usually brought from different regions so that different languages are also different. Keywords: Psychosocial Support, Volunteers, Semeru Eruption